2021
DOI: 10.3390/su13115885
|View full text |Cite
|
Sign up to set email alerts
|

“Trees Are Our Relatives”: Local Perceptions on Forestry Resources and Implications for Climate Change Mitigation

Abstract: The link between nature and society is vital for climate change mitigation and sustainable natural recourse management. Based on a case study of the indigenous people of Mbire in Zimbabwe, we argue that perceptions of indigenous people about forestry resources provide useful pointers toward framing climate mitigation interventions. This interest was necessitated by the growing call to address the suppression of forest-rich indigenous communities in climate change science. Accordingly, the aim of the study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Wynberg et al (2003) also expressed that indigenous fruit trees constitute an essential part of the livelihoods, culture and spirituality of rural communities. Indigenous spirituality can promote sustainable management of trees and ecosystems under climate change (Nalau et al , 2018; Chanza and Musakwa, 2021). This suggests that there are high prospects of embracing climate smart agricultural programs such as agroforestry when working with indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
“…Wynberg et al (2003) also expressed that indigenous fruit trees constitute an essential part of the livelihoods, culture and spirituality of rural communities. Indigenous spirituality can promote sustainable management of trees and ecosystems under climate change (Nalau et al , 2018; Chanza and Musakwa, 2021). This suggests that there are high prospects of embracing climate smart agricultural programs such as agroforestry when working with indigenous communities.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous forest conservation is widely reported as an approach to demonstrate the important role played by ILP in climate change mitigation. This is largely in the form of conservation of scared forestry sites and tree species (Salick et al, 2014;Chanza and Musakwa, 2021a;Maru et al, 2023). These can be patches of forests protected by local communities for spiritual and cultural uses and are usually protected from human interference, making them distinctively unique from other legally conserved areas.…”
Section: Categorymentioning
confidence: 99%
“…In Ethiopia, Maru et al (2023) observed that ILK which is attached to sacred forest conservation has encouraged local people to preserve the remnants of natural vegetation thereby contributing to GHG reduction. Chanza and Musakwa (2021a) discovered that indigenous people in some areas of rural Zimbabwe view forests and trees as their own relatives. This belief system is largely common with the elderly citizens who see the loss of trees as an existential threat to their own survival.…”
Section: Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies show that local observations of climate change impacts can improve our understanding of the localized responses of physical and biological systems to climate change [5,15]. This knowledge can also give useful pointers on how to design appropriate climate adaptation and mitigation strategies that are suitable to local socio-ecological systems [16][17][18]. Documenting the local observations of climate change and comparing them with existing knowledge in the traditional climate science domain can strengthen and enrich climate impact assessment studies [15].…”
Section: Introductionmentioning
confidence: 99%